Basic statistics for life scientists : a concise handbook of essential techniques - Tomek, Jakub; Eisner, David (Hoboken ; Bognor Regis : Wiley, 2026)
Basic statistics for life scientists is an approachable, concise handbook of essential statistical techniques that teaches correct practice in the life sciences and related fields, helping readers become competent users of statistics and assisting them in identifying the best statistical method for their research question while also being aware of its strengths and limitations. The book is supported by illustrations and real-world examples explaining how to apply the techniques using statistical software tools. Written by two highly qualified authors, Basic statistics for life scientists includes information on: appropriate statistical techniques for evaluating experimental data, avoiding excessive jargon or mathematics, misuse of statistical techniques in life sciences research, systematic problems present in life sciences research, such as multiple hypothesis testing and pseudoreplication, experimental design and the problems associated with the concept of binary statistical significance. Basic statistics for life scientists is an essential reference for students and researchers in life sciences and biomedicine, especially PhD students and postdoctoral researchers, seeking to confidently apply appropriate statistical tests to their data.
Publikace Basic statistics for life scientists je přehledná a srozumitelná příručka základních statistických metod určená především studentům a výzkumníkům v biologických, lékařských a dalších přírodovědných oborech. Autoři se zaměřují na praktické pochopení statistiky, nikoli na formální matematický aparát, a kladou důraz na správnou interpretaci dat a výsledků. Kniha systematicky vysvětluje základní pojmy statistického popisu dat, pravděpodobnosti, testování hypotéz, intervaly spolehlivosti a základy regresní analýzy. Text je doplněn ilustracemi, grafy a praktickými příklady z oblasti life sciences, které usnadňují porozumění a aplikaci probíraných metod v reálném výzkumu. Publikace je vhodná jako studijní materiál i jako rychlá referenční příručka pro každodenní práci s experimentálními daty.
Obsahuje QR kód s odkazem na doprovodný materiál
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: biologie; přírodní vědy; vědecký výzkum; statistické metody; analýza dat; statistické metody v biologii; monografie; příručky; biology; natural sciences; scientific research; statistical methods; data analysis; monographs; handbooks and manuals